Fabrication of Soft and Wearable Electrostatic Generator Based on Streaming Electrification - Shota Kamiyauchi; Yuki Yokoyama; Yu Kuwajima; Yumeta Seki; Satoshi Awaki; Shingo Maeda; Hiroki Shigemune (Advanced Intelligent Systems, 2022)
Electrostatic actuators, which are characterized by low weight, power consumption, noise, and remaining heat, have been studied widely and are expected to find use in wearable devices. However, they require high‐voltage control and safety circuits, which may increase their bulk. Herein, a soft electrostatic generator is proposed for use in wearable devices. Specifically, streaming electrification is used, wherein electric charge is generated through the interactions between a fluid and a solid material (the developed system is named a “streaming electrification generator”). The contact area with the insulating fluid is increased by using a porous material, and the amount of charge generated is increased to the level needed to drive electrostatic actuators using materials with different dielectric characteristics. Moreover, the generator is made of soft materials and therefore can adapt to the shape of the human body and not interfere with its movement. Finally, it is ideal for wearables because it does not use materials that are harmful to the human body. Thus, the developed system, which is made of soft materials, is a novel power generator and should be suitable for electrostatic actuators used in wearable devices.